Review of Michalowskiya Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Dikraneurini) with description of six new species from China - Kang, Juxia; Zhang, Yalin (Zootaxa, 2013)
A key to known species of the subgenus Michalowskiya (Michalowskiya) Dworakowska is provided. Detailed morpho-logical descriptions and illustrations of six new species, Michalowskiya (Michalowskiya) aurantiaca, M. (M.) biprocessa, M. (M.) breviprocessa, M. (M.) brownistriata, M. (M.) longiprocessa, and M. (M.) pedata spp. nov. from China are pro-vided.